Penilaian Kamuflase Cecak Rumah Hemidactylus frenatus Duméril & Bibron, 1836 - Fathoni, R.M. Farchan; Susilohadi, S (Bioma : Berkala Ilmiah Biologi, 2020)
Hemidactylus frenatus has 2 color morph, those  are dark morph and light morph. This gecko also has the ability to change it’s body color  from one morph to another. This ability is usually associated with thermoregulation effort or camouflage for defense. This research attempts to assess the camouflage of the house gecko on various habitat type (building and garden) that exist on UGM campus. By employing CBIR method, it is found that this gecko has high similarity with it’s surrounding, either on the light background (building) or dark background (garden). This is shown by the Euclidean distance value at 0.36 on the gecko that lives on the buildings, and 0.13 on the gecko that lives on the garden. According to the observation and literature study, it is found that the rapid color change ability on this gecko is not related to thermoregulation but more likely associated with camouflage. The type of camouflage strategy employed by Hemidactylus frenatus is background matching